2015
DOI: 10.1038/jid.2015.85
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Expression and Regulation of Interleukin-33 during Homeostasis and Inflammation: Strong Species Differences

Abstract: IL-33 is a novel IL-1 family member with a putative role in inflammatory skin disorders and a complex biology. Therefore, recent conflicting data regarding its function in experimental models justify a close assessment of its tissue expression and regulation. Indeed, we report here that there are strong species differences in the expression and regulation of epidermal IL-33. In murine epidermis, IL-33 behaved similar to an alarmin, being constitutively expressed in keratinocyte nuclei and rapidly lost during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 36 publications
7
61
0
Order By: Relevance
“…IL-33 expression in CP in human has recently been described by Malcolm et al in gingival epithelial cells and our results confirmed this observation [20]. This is of particular interest because differences of IL-33 expression in skin have been reported between species [35]. Notably in human and porcine keratinocytes, IL-33 expression is low but rapidly induced after skin wounding whereas it is the opposite in mice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…IL-33 expression in CP in human has recently been described by Malcolm et al in gingival epithelial cells and our results confirmed this observation [20]. This is of particular interest because differences of IL-33 expression in skin have been reported between species [35]. Notably in human and porcine keratinocytes, IL-33 expression is low but rapidly induced after skin wounding whereas it is the opposite in mice.…”
Section: Discussionsupporting
confidence: 90%
“…We also recorded such increase 24 hours after Pg infection of human epithelial cells. However, as we also recorded an increased IL-33 expression in vivo independently of Pg infection, it is tempting to speculate that the ligature apposition is an inflammatory stimulus sufficient to induce the increase of IL-33 expression in gingival epithelial cells, directly or throughout other pro-inflammatory cytokines such as TNF-α or IFN-γ [35, 37]. Consistently, we have also observed an IL-33 expression in Sham animals subjected to a slight incision suggesting that this mechanical stimulus may trigger the production of IL-33 in gingival epithelial cell and that Pg may be not the major factor needed for IL-33 expression.…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 expression in endothelial cells in vitro has been linked to cellular quiescence and confluence, and may require Notch signals (Küchler et al, 2008; Sundlisaeter et al, 2012). Human and mouse share constitutive IL-33 expression at epithelial surfaces, including in skin, stomach, intestine, salivary gland, vagina and lung, where expression is particularly high in alveolar type 2 cells (Mohapatra et al, 2015; Moussion et al, 2008; Pastorelli et al, 2010; Schmitz et al, 2005); species-specific differences may exist (Sundnes et al, 2015). This epithelial expression pattern partially overlaps with other cytokines that target ILC2s, including TSLP and IL-25, suggesting potentially shared functions (Bulek et al, 2010; Mohapatra et al, 2015).…”
Section: Sources and Production Of Il-33mentioning
confidence: 99%
“…mast cells, macrophages and DCs. IL-33 can be induced by a variety of immune stimuli, for example proinflammatory TLR ligands, cytokines and immune complexes [7] [8]. Different IL-33 splice variants have been observed in human tissues.…”
Section: Il-33mentioning
confidence: 99%
“…Although it seems from these reports that IL-33 signalling at the site of cutaneous damage may facilitate the transition of macrophages from a pro-inflammatory to a prorepair phenotype thereby promoting dermal wound healing, the underlying mechanism for IL-33 in skin wound healing remains unclear. Given the interesting observation that IL-33 expression both varies at a basal level and is also differentially regulated between mouse and human keratinocytes [8], it is clear that more detailed studies need to be performed on human tissues and human cell lines to fully elucidate the role of IL-33 in cutaneous wound healing in humans.…”
Section: Il-33 In Cutaneous Wound Healingmentioning
confidence: 99%